How to reduce self-stigma in schizophrenia? - an intervention through sociodrama and e-learning - Sousa, S.D. (2019)
Self-stigma is a personal response to perceived mental illness stigma (Corrigan & Watson, 2002). Applying recovery to persons with mental illnesses such as schizophrenia, implies working with Self-Stigma, in the sense that is one of the major obstacles to social integration and to active life (Brohan et al., 2011; Corrigan & Kleinlein, 2005; Goffman, 1991). Research on strategies for changing self-stigma can be focus on new and innovative programs, like the one we will present, based on group intervention (sociodrama) and individual intervention (e-learning).